Barotropic and baroclinic semidiurnal tidal currents in two contrasting coastal upwelling zones of Chile. Issue 3 (14th March 2013) - Bravo, L.; Ramos, M.; Sobarzo, M.; Pizarro, O.; Valle‐Levinson, A.
ABSTRACT: [1] Current velocity observations from the continental shelves of Coquimbo (~30°S) and Concepcion (~36°30'S), central Chile, were analyzed to evaluate the role of water column stratification and shelf width on baroclinic semidiurnal tidal currents. Semidiurnal barotropic currents off both zones were typically < 5 cm/s, but depth‐dependent semidiurnal flows could exceed 10 cm s ‐1 during stratified conditions. Both zones are recognized as pronounced upwelling centers, with maximum upwelling‐favorable winds in spring and summer, respectively. At the northern zone, stratification was mainly controlled by temperature differences between surface and bottom waters with maximum stratification during summer. The southern zone showed more stratification during winter because of freshwater input from local rivers. Consequently, greater variability in the baroclinic semidiurnal currents was observed during summer at the northern continental shelf and in winter at the south. In both regions, much of the semidiurnal variability was consistent with an internal wave's first baroclinic mode of wavelengths of ~10–13 km. Nevertheless, during the period of maximum energy fluxes off the north, the second baroclinic mode (wavelength ~7 km) was also important and matched periods of low upwelling index (relaxation of upwelling favorable winds). Typical energy fluxes during summer integrated in the water column, related to the semidiurnal internal tides were 0.12 W/m of the northern site and 0.1 W/m off the southern site. Possible sites of internal wave generation off the south were the Biobío submarine canyon and the slope/shelf break, while off the north, the generation site was the slope/shelf break. Key Points: The variability of baroclinic semidiurnal currents were modulated by upwelling High dynamical modes were important when existed a supercritical topography In upwelling zones the internal wave could contribute to biological productivity